Incidence of ash dieback in the Left-Bank Forest-Steppe depending on stand characteristics - Meshkova, V. L.; Borysova, V. L. (Forestry and Forest Melioration, 2020)
The incidence of ash dieback in the forest-steppe part of Sumy and Kharkiv Regions was analysed taking into account the type of forest site conditions, the stand age, relative stocking density, site index class and the proportion of European ash in the stand composition. Ash dieback is quite widespread in inspected stands of the Left-Bank Forest-Steppe of Sumy and Kharkiv Regions. The disease spreads similarly in natural and artificial stands. It was more often revealed in the fresh fertile forest site conditions, however, such forest site conditions are the most spread and the most favourable for European ash. It was found that ash dieback incidence tends to grow with a stand aging and lasts up to the stand’s age of 80. It can be explained by the development of stem and collar rots which occur later. Ash dieback incidence is the highest in the stands with 40–70 % of ash in their composition, at a relative density of stocking over 0.5 in the stands of different site index classes.